MANAGEMENT OF PUBLIC PERCEPTIONS IN IMPROVING THE QUALITY OF HEALTH SERVICES AT THE LAMBU DISTRICT HEALTH SERVICE, BIMA DISTRICT - Nurbaety; Mujiburrahman (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
Abstract The purpose of this study is to determine the public's perception of enjoying health services, then this type of research is a quantitative method with a descriptive analysis approach. In determining the population and samples, the quota sampling technique was used by determining the number of respondents based on the quota sample set as many as 30 people who were taken by accident. The results of the research are that the current health service at the Lambu Health Center is basically a national task that is the responsibility of the government, both at the central, regional and sub-district levels to the village/village. In order to carry out the function of health services to the community at the sub-district level, health workers at the Lambu Health Center have done well. Furthermore, the conclusion is the public perception of health services at the community health center in the Lambu sub-district based on the answers from respondents who answered very well 30.00% then respondents who answered well 65.00% then respondents who answered quite well 5.00% and respondents who answered no good 0.00%. Related to services, of course, it has advantages and disadvantages which lie in the willingness to provide assistance to the community without being asked to be corrected, even though the weaknesses referred to are not solely based on health workers. Keywords: management, perception, service quality, health.